Ritual in Transfigured Time: Narcisa Hirsch, Sufi Poetry, Ecstatic Dances, and the Female Gaze - Silvina Szperling (The International Journal of Screendance, 2017)
No abstract available This article was originally published by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as part of The International Journal of Screendance, Volume 3 (2013), Parallel Press. It is made available here with the kind permission of Parallel Press.